The European Community's Trade and Trade-Related Industrial Policies - Xafa, Miranda; Kronenberg, Roger; Landell-Mills, Joslin (Washington, D.C. : International Monetary Fund, 1992)
This paper examines the objectives and instruments of trade policy in the European Community (EC) from 1987 until mid-1992. It reviews the Community's institutional setting and policy environment as background to recent trends in EC trade policies and trading arrangements. A discussion of key issues and developments in the internal market program and its interactions with the Uruguay Round of multilateral trade negotiations is followed by a review of the main issues underlying trade disputes with third countries and trade-related industrial policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet